Are Classic Bedside Exam Findings Required to Initiate Enteral Nutrition in Critically Ill Patients: Emphasis on Bowel Sounds and Abdominal Distension. (9th December 2020) - Deane, Adam M.; Ali Abdelhamid, Yasmine; Plummer, Mark P.; Fetterplace, Kate; Moore, Cara; Reintam Blaser, Annika
Abstract: The general physical examination of a patient is an axiom of critical care medicine, but evidence to support this practice remains sparse. Given the lack of evidence for a comprehensive physical examination of the entire patient on admission to the intensive care unit, which most clinicians consider an essential part of care, should clinicians continue the practice of a specialized gastrointestinal system physical examination when commencing enteral nutrition in critically ill patients? In this review of literature related to gastrointestinal system examination in critically ill patients, the focus is on gastrointestinal sounds and abdominal distension. There is a summary of what these physical features represent, an evaluation of the evidence regarding use of these physical features in patients after abdominal surgery, exploration of the rationale for and against using the physical findings in routine practice, and detail regarding what is known about each feature in critically ill patients. Based on the available evidence, it is recommended that an isolated symptom, sign, or bedside test does not provide meaningful information. However, it is submitted that a comprehensive physical assessment of the gastrointestinal system still has a role when initiating or administering enteral nutrition: specifically, when multiple features are present, clinicians should consider further investigation or intervention.